Smart tourism technologies, sustainability awareness, and the paradox of revisit intention: Evidence from Indonesia’s marine destinations - Ratnasari, Warti; Kusmaningtyas, Amiartuti; Cempena, Ida Bagus (Edelweiss Applied Science and Technology, 2025)
Digital transformation is playing an increasingly significant role in the development of tourism in emerging destinations, where Smart Tourism Technologies (STTs) serve as essential tools for enhancing visitor experiences and promoting sustainable management. This study investigates how STTs influence the formation of memorable tourist experiences, satisfaction with destinations, and intentions to revisit, considering both the moderating and direct effects of over-tourism awareness at sea destinations in Indonesia. A survey and evaluation were conducted on 385 visitors to Derawan, Maratua, and Kaniungan Islands using Partial Least Squares–Structural Equation Modelling (PLS-SEM). The findings indicate that both exploitative and explorative types of STT use significantly improve memorable experiences, which subsequently increase satisfaction with the destination. Destination satisfaction is identified as the most significant predictor of the intention to return, whereas awareness of over-tourism affects revisit intention directly but does not moderate the relationship between satisfaction and loyalty. These results highlight a sustainability contradiction where travelers are eager to explore destinations despite being aware of over-tourism issues. The study enhances theory by broadening the Theory of Planned Behaviour (TPB) and the Theory of Reasoned Action (TRA) to include digital and sustainability aspects. It provides strategic advice for destination managers and policymakers to utilize immersive STTs not only to sustainably improve the tourist experience but also to incorporate sustainability awareness into digital platforms.